Biotransformation of benzimidazole anthelmintics in reed (Phragmites australis) as a potential tool for their detoxification in environment - Podlipná, Radka; Skálová, Lenka; Seidlová, Helena; Szotáková, Barbora; Kubíček, Vladimír; Stuchlíková, Lucie; Jirásko, Robert; Vaněk, Tomáš; Vokřál, Ivan (Bioresource technology, 2013)
Benzimidazole anthelmintics, the drugs against parasitic worms, are widely used in human as well as veterinary medicine. Following excretion, these substances may persist in the environment and impact non-target organisms. In order to test phytoremediation as a possible tool for detoxification of anthelmintics in environment, the biotransformation pathways of albendazole (ABZ) and flubendazole (FLU) were studied in reed (Phragmites australis) in vitro. Reed cells were able to uptake and biotransform both anthelmintics. Ten ABZ metabolites and five FLU metabolites were found. Some atypical biotransformation reactions (formation of glucosylglucosides, acetylglucosides and xylosylglucosides), which have not been described previously, were identified. Based on the obtained results, the schemes of metabolic pathways of ABZ and FLU in reed were proposed. Most of ABZ and FLU metabolites can be considered as anthelmintically less active; therefore uptake and biotransformation of these anthelmintics by reed could be useful for decrease of their toxicity in environment.
Keywords: Benzimidazoles; Metabolic Networks and Pathways; Anthelmintics; biodegradace; Phytoremediation; benzimidazoly; mebendazol; Flubendazole; Mebendazole; metabolické sítě a dráhy; lidé; Inactivation, Metabolic; Drug-metabolism; Albendazole; metabolická inaktivace; Poaceae; biotransformace; lipnicovité; anthelmintika; Biodegradation, Environmental; Biotransformation; Phytotransformation; albendazol; Humans